2022
DOI: 10.2147/jir.s352863
|View full text |Cite
|
Sign up to set email alerts
|

Ban-Lan-Gen Granule Alleviates Dextran Sulfate Sodium-Induced Chronic Relapsing Colitis in Mice via Regulating Gut Microbiota and Restoring Gut SCFA Derived-GLP-1 Production

Abstract: GLP-1 based therapy represents a new treatment option for inflammatory bowel disease. Ban-Lan-Gen (BLG) granule, a known anti-viral TCM formulation, exhibits potential anti-inflammatory activities in treating various kinds of inflammation. However, its anti-inflammatory effect on colitis and the underlying mechanisms remain unknown. Methods: Dextran sulfate sodium (DSS)-induced chronic relapsing colitis in mice was established. The disease activity index, histological sign of damage, and levels of proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Consistent with previous studies, we found that the abundance of several beneficial microbes increased while conditional pathogens were reduced in the metformin and pioglitazone monotherapy groups. We found that the abundance of the beneficial microbe Akkermansia increased in the metformin monotherapy group, and the abundance of several harmful microbiota decreased, such as Eubacterium_xylanophilum_group and Oscillibacter ( Qin et al, 2012 ; Kong et al, 2019 ; Gurung et al, 2020 ; Peng et al, 2022 ). Akkermansia increased, particularly during metformin treatment, in clinical and experimental studies and functioned as a SCFAs-producing and mucin-degrading bacterium ( Ke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Consistent with previous studies, we found that the abundance of several beneficial microbes increased while conditional pathogens were reduced in the metformin and pioglitazone monotherapy groups. We found that the abundance of the beneficial microbe Akkermansia increased in the metformin monotherapy group, and the abundance of several harmful microbiota decreased, such as Eubacterium_xylanophilum_group and Oscillibacter ( Qin et al, 2012 ; Kong et al, 2019 ; Gurung et al, 2020 ; Peng et al, 2022 ). Akkermansia increased, particularly during metformin treatment, in clinical and experimental studies and functioned as a SCFAs-producing and mucin-degrading bacterium ( Ke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“…Akkermansia increased, particularly during metformin treatment, in clinical and experimental studies and functioned as a SCFAs-producing and mucin-degrading bacterium ( Ke et al, 2021 ). Eubacterium_xylanophilum_group was found to have increased abundance in ulcerative colitis mice ( Peng et al, 2022 ). Oscillibacter was found a conditional pathogen positively correlated with obesity- and nutrient-related metabolic pathways in high-sucrose diet-fed mice and inflammatory cytokine levels in ulcerative colitis mice ( Kong et al, 2019 ; Peng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 Gavage L. johnsonii increased the B/F ratio (Figure S1M ). The relative abundance of bacteria on the family level showed that L. johnsonii increased the levels of Prevotellaceae 20 and order Clostridia , 21 which were closely related to the secretion of short chain fatty acids (SCFAs), and decreased the levels of Lachnospiraceae, Oscillospiraceae and Erysipelotrichaceae (Figure S1O ). We also determined gavage L. johnsonii could colonize in the colon tissues by qPCR analysis ( Figure 1i ).…”
Section: Resultsmentioning
confidence: 99%